Attributes of Shopping Mall Image, Customer Satisfaction and Mall Patronage for Selected Shopping Malls in Southern Gauteng, South Africa - Dubihlela, Dorah (Journal of Economics and Behavioral Studies, 2014)
This paper identifies the main features of a shopping mall that govern customer satisfaction in Southern Gauteng in South Africa. Literature is reviewed, identifying various features in shopping malls such as merchandisers, accessibility, service, amenities, ambiance, entertainment, security and among others. This literature is based on previous authors’ scientific work, on mall features that influence the satisfaction and patronage by customers. A quantitative study was conducted with 429 questionnaires used in the final data analysis. The study results suggest the important shopping mall features in Gauteng South in South African and confirm that specific shopping mall features are positively related to customer satisfaction and mall patronage. The paper further develops suggestions on mall features that should be emphasised for promotional campaigns, customer satisfaction and mall patronage by customers.